Eight-Year Outcomes of Implantation of Posterior Chamber Phakic Intraocular Lens With a Central Port for Moderate to High Ametropia - Kamiya, Kazutaka; Shimizu, Kimiya; Takahashi, Masahide; Ando, Wakako; Hayakawa, Hideki; Shoji, Nobuyuki (Frontiers in Medicine, 2021)
PURPOSE: To assess the 8-year clinical outcomes of implantation of an ICL with a central port (KS-Aquaport; hole ICL) for moderate to high myopia and myopic astigmatism. METHODS: This retrospective study comprised a total of one hundred seventy-seven eyes of 106 patients with spherical equivalents of -7.99 ± 3.33 D [mean ± standard deviation] who underwent hole ICL implantation. Preoperatively and at 1 month, 1, 2, 4, 6, and 8 years postoperatively, we evaluated the safety, efficacy, predictability, stability, and adverse events of the surgery. RESULTS: LogMAR uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) were -0.07 ± 0.17 and -0.20 ± 0.09, respectively, 8 years postoperatively. The safety and efficacy indices were 1.18 ± 0.24 and 0.89 ± 0.28, respectively. At 8 years, 83% and 93% eyes were within ± 0.5 and ± 1.0 D of the targeted correction, respectively. Change in manifest refraction from 1 month to 8 years postoperatively was -0.13 ± 0.30 D. We found that neither significant IOP rise (including pupillary block) nor significant endothelial cell loss occurred in any case throughout the 8-year observation period. CONCLUSIONS: Current ICL implantation with central port technology offered good continuous outcomes for all measures of safety, efficacy, predictability, and stability for correcting moderate to high myopic errors over a long period, suggesting its long-term viability as a surgical approach for the treatment of such eyes.